PERENCANAAN LABA ATAS PENJUALAN GLASIR KUNING (GK-4) PADA UPT PSTKP BALI-BPPT TAHUN 2015 - I Nyoman Normal (Forum Manajemen, 2015)
The aims of this research that relate profit planning on sales of yellowglazur (GK-4) at UPT PSTKP Bali-BPPT in 2015 years were: (1) To know the BreakEvenPoint(BEP);(2)ToassesstheMarginOfSafety(MOS);(3)TodeterminetheShut-DownPoint(SDP);(4)ToanalizeDegreeofOperatingLeverage(DOL);and(5)To calculate the Contribution Margin each Unit (CMU).The research resultsabout yellow glazur (GK-4) at UPT PSTKP Bali-BPPT in 2015th years shew: (1) Thebreak-Even Point (BEP) was 6.022,05 liter or Rp 437.380.750,00. On the sales of6.022,05 liter or Rp 437.380.750,00, UPT PSTKP Bali-BPPT does not suffer loss anddoes not get profit; (3) The Margin of Safety (MOS) was 7,92%. On that of condition, thUPT PSTKP Bali-BPPT may decrease its sales from budgeted sales maximum 7,92% so that does not suffer loss. If its sales decrease under 7,92%, so the business still getprofit; (4)The Shut-Down Point (SDP) was 2.565,50 liter or Rp 186.550.187,00. Onits sales, the business could not pay cash fixed cost, so that feseable to shut-down;(5) The Degree of Operating Leverage (DOL) was 12,61 times. This condition shewthat if the sales volume increase 1%, so net profit increase 12,61%. Each increasingof sales volume1%, itwillincrease net profit 12,61%; and (6) The ContributionMargin each Unit (CMU) was Rp 16.763,00/liter, that is each sales (1 liter) oftheyellow glazur (GK-4), it would getcontribution margin Rp 16.763,00 each liter.